Soil CO2 Efflux in Agroforestry and Full-Sun Coffee Systems - Gomes, Lucas de Carvalho (2014)
The global climate change has been attributed to increasing greenhouse gas concentration, especially Carbon Dioxide (CO2) in atmosphere as result of human activities. To mitigate this effect, there is a global effort to reduce CO2 emissions and develop technologies to remove part of this gas from the atmosphere. The most simple and natural way to remove CO2 from atmosphere is carried out by plants through photosynthesis. This process removes carbon from atmosphere creating vegetal biomass, which later will be deposited in soil, the biggest reservoir of carbon in the terrestrial biosphere (2500 GtC). The balance of carbon in the soil is the result of input of vegetal biomass and the output of carbon, especially as CO2. Therefore, the soil, in the Global Carbon Cycle, acts either as source or as a sink of carbon from the atmosphere. To better understand the role of soil in Carbon Cycle and to it become sink of CO2 it is not enough to know the carbon that particular plant species can deposit in the soil, but also how this carbon is released back to atmosphere. The CO2 is released from soil (also called soil CO2 efflux) mainly from soil respiration, which is the biggest source of CO2 from terrestrial biosphere. Soil CO2 efflux is a complex process that depends on the soil biological and physical characteristics and especially on the soil temperature and moisture conditions. However, the vegetation type and the agricultural practices may be the main components to control the soil CO2 efflux in agroecosystems, because they influence the soil biological and physical characteristics and control the soil temperature and moisture conditions. Agroforestry coffee management increases the amount of organic matter residue and the canopy’s trees protect the soil against the directly solar radiation, thus, affecting the soil CO2 efflux. The general objective of this study it was to understand how the canopy’s trees in agroforestry and full-sun coffee systems affect the soil CO2 efflux and which factors control it. To this end we evaluated the soil CO2 efflux (in situ) in agroforestry and full-sun coffee systems in three different farms in Zona da Mata of Minas Gerais, Brazil. The increase in canopy cover levels from trees leads to increase soil moisture and decrease air and soil temperature at 5 and 10 cm depth. The effect of trees on microclimate did not affect the daily average of soil CO2 efflux between agroforestry and full-sun coffee systems, but they showed different daily emission dynamics. In agroforestry system the soil CO2 efflux was more stable during the day, presenting less variation from morning to midday and higher spatial variation than the full-sun system. In agroforestry system the variation of soil CO2 efflux was explained mainly by total nitrogen and labile carbon and in full- sun system by soil temperature at 10 cm depth. The principal components analysis shows that in general the soil CO2 efflux was positively correlated with soil temperature at 5 and 10 cm depths and negatively correlated with soil moisture. In conclusion, the trees in agroforestry coffee systems promoted stability to microclimate and soil CO2 efflux compared to Full-Sun systems.